Long-term behaviour of non-functioning pituitary microadenomas: experience from a tertiary care centre in Romania - Iftimie, Mădălina Elena; Burcea, Iulia Florentina; Dobre, Ramona; Pigni, Stella; Prodam, Flavia; Poiană, Cătălina (Frontiers in Endocrinology, 2025)
ObjectiveAn optimal surveillance plan of micro-nonfunctioning pituitary adenomas (micro-NFPAs) is not well established despite high prevalence and increasing incidence of these tumors. This study aims to characterize the natural history of conservatively treated micro-NFPAs and provide evidence for a management algorithm.MethodsRetrospective, single center cohort study that analyzed clinical, hormonal and imaging data of conservatively managed micro-NFPAs (years 2018-2023).Results371 patients with micro-NFPAs were included in the study (mean age at diagnosis 41.26 ± 13.71 years, 91.6% females) with a mean tumor size at detection of 5.51 ± 1.95 mm. Over a median follow-up period of 4.8 years (IQR 2-8.64): 23.7% of all micro-NFPAs were stable, 41% regressed and 35.3% had any progression in size (34.5% of patients had a significant tumor growth, when considering 1 mm enlargement as significant, with a growth incidence of 17.18 per 100 person-years, 95% CI: 14.2- 20,15). The median growth was 1 mm (IQR: 0.5-2) over the entire follow up period and only 2.42% microadenomas evolved into macroadenomas, without clinical consequences. Sex, BMI, age were not predictors of tumor growth, however tumors smaller than 6 mm had a 47.4% higher incidence rate of significant tumor growth (≥ 1mm) events per 100 person-years, compared to larger microadenomas. Alternating CT with MRI during follow-up is an important predictor for tumor variability. Median time until growth was 11.32 months (95%CI: 9.66- 12.97). At diagnosis, 1.1% had secondary hypogonadism, 1.1% hypothyroidism and 0.5% secondary hypoadrenalism. During follow-up, only 5 patients (1.3%) developed hypopituitarism after a median of 2 years (0.9-5.1), irrespective of tumor enlargement or other demographic and clinical factors.ConclusionMicro-NFPAs have an overall benign clinical course, with a high measuring variability in tumors smaller than 6 mm and hypopituitarism is a very rare occurrence. Performing the first follow-up MRI at one year and if stable, delaying re-evaluation to 5 years, without pituitary function reassessment in absence of clinical manifestations, is a safe and cost-effective approach.